Effects of Helicobacter pylori Infection on Gastric Parietal Cells and E-cadherin in Mongolian Gerbils - Motonobu Murakami; Mayu Fukuzawa; Mika Yamamoto; Kanako Hamaya; Yuumi Tamura; Akiko Sugiyama; Rei Takahashi; Toshiko Murakami; Kikuko Amagase; Koji Takeuchi (Elsevier, 2013)
Abstract.: Atrophic gastritis caused by infection with Helicobacter pylori is characterized by parietal cell loss, which is a main risk factor for gastric cancer. Parietal cells play a crucial role in the regulation of cell lineage maturation and proliferation in the gastric units. Among the classical cadherins, E-cadherin plays an important role not only in epithelial cell-cell connections, but also in the maintenance of epithelial polarity and gastric glandular architecture and regulation of cell proliferation. The aim of this study is to elucidate how parietal cells and E-cadherin are altered in gastritis with Helicobacter pylori infection. We studied the effects of Helicobacter pylori on gastric mucosal E-cadherin 2 weeks after inoculation and investigated the relationship between parietal cell loss and the amount of E-cadherin on parietal cells in Mongolian gerbils. The number of parietal cells and amount of staining of E-cadherin below the isthmus were investigated by immunohistochemistry. It was shown that a reduction in intercellular E-cadherin preceded the disappearance of parietal cells. The gastric glands where parietal cells were lost were replaced by mucus secreting cells without E-cadherin. These results suggest that Helicobacter pylori damaged E-cadherin on parietal cells and caused massive parietal cell loss, leading to the deregulation of gastric morphology. Keywords:: Helicobacter pylori, E-cadherin, gastritis, parietal cell, gastric